DAYA TERIMA DAN KANDUNGAN PROTEIN BISKUIT SUBSTITUSI TEPUNG UBI JALAR UNGU DAN ISOLAT PROTEIN KEDELAI UNTUK PEMBERIAN MAKANAN TAMBAHAN IBU HAMIL KEK - Iga Ayuni Fatmala; Annis Catur Adi (Media Gizi Indonesia, 2017)
The use of purple sweet potato fl our and soy protein isolates to be processed into protein biscuit has a good potential to be an appropriate supplementary food for chronic energy deficiency (CED) pregnant woman compared to biscuits commercialized on market. This research aimed to investigate the acceptance and protein content of biscuits that had been substituted with purple sweet potato fl our and soy protein isolates. This research was true experimental design with completely randomized design (RAL) with 6 repetitions. There was 3 formulas which were 1 control formula (F0) and 2 modified formulas (F1, F2). The total of purple sweet potato fl our substitution on F1 was 170 g and F2 was 90 g, meanwhile the total of soy protein isolate substitution on F1 was 30 g and F2 was 10 g. The data was analyzed by applying descriptive analyses which was tested by Kruskal Wallis and Mann Whitney to find the effect among formulas. The result of this research showed that generally the assessment of biscuit was well accepted by pregnant woman and the highest average of acceptance was F2 formula. The assessment of the highest acceptance for color and aroma characteristic was F2. The assessment of color, aroma, and taste among formulas had no significant impact (α<0.05), meanwhile on texture characteristic there was significant effect (α>0.05). The best formula (F2) has a good acceptance and posses protein content of 11.9 g per 100 g that can fulfill the need of 10% protein for pregnant woman so it can be used as supplementary food for pregnant woman.